Learner- vs. expert-constructed outlines: Testing the associations with L2 text comprehension and multiple intelligences - Moradi, Sholeh; Ghahari, Shima; Abbas Nejad, Mohammad (Studies in Second Language Learning and Teaching, 2020)
Cognitive organizers (COs) are text aids which represent objects, concepts, and their relations by the use of symbols and spatial arrangements without adding to semantic content. The present study examines language learners’ text comprehension through outlines, a popular CO, compared with text-only condition, and further investigates the effect of learner-constructed outlines (i.e., systematic note-taking) and expert-constructed outlines (i.e., readymade displays) on comprehension. Finally, the predictive power of multiple intelligences (MI) across different input modalities is scrutinized. Following stratified random sampling, a total of 111 EFL undergraduates were divided into text-only (receiving a text twice), expert-constructed (the text followed by an outline), and learner-constructed (the text followed by an outline to be drawn up by the learner) groups. A TOEFL examination, a 1218-word expository text on systematic sleep disorder, a follow-up reading comprehension test, and a multiple intelligences inventory constituted the data collection measures. The results of multiple regression and ANOVA were as follows: (a) COs lead to more content recall than text displays; (b) expert-constructed and learner-constructed outlines are equally effective; (c) MI significantly predicts the groups’ reading comprehension; (d) interpersonal and intrapersonal intelligences are significant correlates of text-only groups’ performance; and (e) visual, verbal, and intrapersonal intelligences are significantly associated with learner-constructed groups’ reading scores. The study offers several implications for theory and practice.